Assessing the antecedents of customer loyalty on healthcare insurance products: Service quality; perceived value embedded model - Abdelfattah, Fadi Abdelmuniem (OmniaScience, 2018)
This research aim to investigate the influence of service quality attributes towards customers’ loyalty on health insurance products. In addition, this research also tested the mediation role of perceived value in between service quality and customers’ loyalty on health insurance products. Design/methodology/approach: Based on the literature review, this research developed a conceptual model of customers loyalty embedded with service quality and perceived value. The study surveyed 342 healthcare insurance customers. Apart from assessing the reliability and validity of the constructs through confirmatory factor analysis, this research also used structural equation modelling (SEM) approach to test the proposed hypothesis. Findings: The results from the inferential statistics revealed that the healthcare insurance customers are highly influenced by service quality followed by the perceived value in reaching their loyalty towards a particular health insurance service provider. Research limitations/implications: The sample for this study is based on health insurance customers only and it is suggested that future studies enlarge the scope to include others type of customers of different insurance products. Practical implications: In order to encourage the customers to more loyal towards their service providers, this research will add value for the mangers to understand the items of service quality and considering the perceived value of the target customers in order to optimize their loyalty. As whole, the outcome of this research will assist managers for better understanding of the customers’ loyalty antecedents under the perspective of healthcare insurance products. Originality/value: This paper has tried to provide a comprehensive understanding about customers’ loyalty under the perspective of service quality and perceived values context in the Malaysian health care insurance industry. Since there was a lack of such research in Malaysian health insurance context, this research can provide theoretical contribution and managerial basis for future researches as well as implications for the managers. Yet, till now research in this sector under Malaysian context do not appear adequately to take into account service quality, perceived values and customers loyalty factors.